1978
DOI: 10.1083/jcb.77.1.148
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of germinal centers in mouse spleen, with special reference to "follicular dendritic cells"

Abstract: Lymphocyte proliferation in germinal centers (GC's) is thought to be triggered by antigen retained extracellularly on the surface of special "dendritic" cells. The anatomy and function of these cells have not been studied directly or in detail. We therefore examined mouse spleen GC's developing in response to sheep erythrocyte stimulation.We found that distinctive "follicular dendritic cells" (FDC's) were present in both the GC and adjacent mantle region of secondary follicles. The large, irregularly shaped nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(71 citation statements)
references
References 23 publications
3
66
1
1
Order By: Relevance
“…On the basis of the present findings, it may be concluded that most of the new primary follicles are "de novo" formed at the site with no relation to the pre-existing follicles. Since many of the new primary follicles develop germinal centers in their medullary pole rather soon after their formation, the formation of the follicles appears to be accompanied by the acquisition of a capacity to develop germinal centers, possibly due to the development of follicular stroma with dendritic cells (WILLIAMS and NossAL, 1966;NOSSAL and ADA, 1971;HOEFSMIT, 1975;CHEN et al, 1978;HOEFSMIT et al, 1982). HOWever, the precise mechanism underlying the formation of new lymph follicles still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the present findings, it may be concluded that most of the new primary follicles are "de novo" formed at the site with no relation to the pre-existing follicles. Since many of the new primary follicles develop germinal centers in their medullary pole rather soon after their formation, the formation of the follicles appears to be accompanied by the acquisition of a capacity to develop germinal centers, possibly due to the development of follicular stroma with dendritic cells (WILLIAMS and NossAL, 1966;NOSSAL and ADA, 1971;HOEFSMIT, 1975;CHEN et al, 1978;HOEFSMIT et al, 1982). HOWever, the precise mechanism underlying the formation of new lymph follicles still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This was observed in vivo on "dendritic macrophages" (now called follicular dendritic cells, FDCs) (15). I did manage to show with Lei Chen that persistence in vivo is truly on the cell surface of the FDC (16,17). This meant that FDCs are very different from macrophages, on which I had failed previously to show retention of intact antigen and immune complexes in spite of large amounts of endocytosis (18).…”
Section: Wwwannualreviewsorg • Decisions On Dendritic Cellsmentioning
confidence: 99%
“…Furthermore, there might be differential expression of proteases that process CXCL13 in lymphoid tissue microcompartments, with a higher concentration of proteases in the surrounding paracortices relative to the inside the GCs. Such compartmentalization of proteases would be consistent with the ability of GCs to harbor immune complexes on FDC surfaces for long periods of time (25)(26)(27), and it is possible that FDCs also serve a depot function for CXCL13 as well. Regardless of the mechanism(s), the compartmentalization of CXCL13 within lymphoid tissue GCs is consistent with its role in bringing T fh cells, B cells, and DCs together.…”
Section: Discussionmentioning
confidence: 86%